Microenvironmental networks promote tumor heterogeneity and enrich for metastatic cancer stem-like cells in Luminal-A breast tumor cells - Weitzenfeld, Polina (Oncotarget, 2016)
The roles of the tumor microenvironment (TME) in generating intra-tumoral diversity within each specific breast cancer subtype are far from being fully elucidated. In this study, we exposed Luminal-A breast cancer cells in culture to combined “TME Stimulation”, representing three typical arms of the breast TME: hormonal (estrogen), inflammatory (tumor necrosis factor α) and growth-promoting (epidermal growth factor). In addition to enriching the tumor cell population with CD44+/β1+ cells (as we previously published), TME Stimulation selected for CD44+/CD24(low/−) stem-like cells, that were further enriched by doxorubicin treatment and demonstrated high plasticity in vitro and in vivo. Knock-down experiments revealed that CD44 and Zeb1 regulated CD24 and β1 expression and controlled differently cell spreading and formation of cellular protrusions. TME-enriched CD44+/CD24(low/−) stem-like cells promoted dissemination to bones and lymph nodes, whereas CD44+/β1+ cells had a low metastatic potential. Mixed co-injections of TME-enriched CD44+/CD24(low/−) and CD44+/β1+ sub-populations generated metastases populated mostly by CD44+/CD24(low/−)-derived cells. Thus, combined activities of several TME factors select for CD44+/CD24(low/−) stem-like cells that dictate the metastatic phenotype of Luminal-A breast tumor cells, suggesting that therapeutic modalities targeting the TME could be introduced as a potential strategy of inhibiting the detrimental stem-like sub-population in this disease subtype.